Synthesis of 2-(4-Allyl-2-Methoxy Phenoxy)-N,N-Bis(2- Hydroxyethyl) Acetamide from the Transformation of Eugenol Isolated from Clove Oil - ginting, mimpin (Journal of Chemical Natural Resources, 2019)
Eugenol as the main component of clove oil has been isolated through NaOH salting procedure followed by H2SO4hydrolysis, n-hexane partitioning and purification with vacuum distillation. 71% (v/v) eugenol was produced with purity of 97.70% based on gas chromatography analysis. 2-(4-allyl-2-methoxy phenoxy)-N,N-bis(2-hydroxyethyl) acetamide compound has the potential as antibacterial or substances for medicine in pharmaceutical can be synthesized from eugenol isolated through alkoxylation, esterification and followed by amidase. Alkoxylation was done using Williamson method through NaOH transformation of hydroxyl functional group in eugenol to form sodium eugenolate then with Î±-monochloroacetate substitution in reflux condition, eugenyl acetate was produced. The acid produced was extracted with ether/Na2CO3, followed by recrystallization using hot water and produced 70.52% solid form. Eugenyl acetate esterification with methanol in benzene solvent with H2SO4 catalyst in reflux condition produced methyl eugenol acetate liquid with 81.36% of yield. Amidase of methyl eugenol acetate with diethanolamine and sodium methoxide catalyst with methanol solvent in reflux condition. After purification, 2-(4-allyl-2-methoxy phenoxy)-N,N-bis(2-hydroxyethyl) acetamide compound in solid form is produced with 72.99% yield. Eugenol isolated, eugenyl acetate and methyl eugenol acetate had their structures analyzed with FT-IR spectroscopy while 2-(4-allyl-2-methoxy phenoxy)-N,N-bis(2-hydroxyethyl) acetamide compound was analysed using FT-IR and H1-NMR.